A molecular method for a qualitative analysis of potentially coding sequences of DNA - Christoffersen,M. L. (2004)
Total sequence phylogenies have low information content. Ordinary misconceptions are that character quality can be ignored and that relying on computer algorithms is enough. Despite widespread preference for a posteriori methods of character evaluation, a priori methods are necessary to produce transformation series that are independent of tree topologies. We propose a stepwise qualitative method for analyzing protein sequences. Informative codons are selected, alternative amino acid transformation series are analyzed, and most parsimonious transformations are hypothesized. We conduct four phylogenetic analyses of philodryanine snakes. The tree based on all nucleotides produces least resolution. Trees based on the exclusion of third positions, on an asymmetric step matrix, and on our protocol, produce similar results. Our method eliminates noise by hypothesizing explicit transformation series for each informative protein-coding amino acid. This approaches qualitative methods for morphological data, in which only characters successfully interpreted in a phylogenetic context are used in cladistic analyses. The method allows utilizing character information contained in the original sequence alignment and, therefore, has higher resolution in inferring a phylogenetic tree than some traditional methods (such as distance methods).